THE MORPHOLOGY AND COMPOSITION OF LIBERIA PLACER GOLD - Mikhailov , V.; Guliy, V.; Kovtun, O.; Sydorchuk, V.; Nakonechna, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Due to civil war in Liberia, which lasted from 1989 to 2003, the geological study of the country was suspended, and became possible only after its end. That is why today, Liberia has no specific geological zoning of the gold-bearing regions. The morphology of gold of Liberia is examined very poorly, and Soviet literature paid no attention to studying this issue. This article is devoted to the study of morphological forms of gold from different regions of the Republic of Liberia.The main objectives of the morphological analysis are to distinguish the main morphological types of gold of the country and their origin and to identify possible ways of placer formation. For achieving more accurate results, roentgenospectrographic and roentgen-fluorescent analyses were carried out. The comparative analysis of the morphological features and the fineness of gold was held in eight regions: Kolahum, Magua, Konia and Zeya in the northern part of the country, Solo and Eastern in its southern part, Soso in the western part, and Timbo in the central part of Liberia. Different types of the gold under study were distinguished according to their morphological features which may indicate their genesis. Well-flattening of grains indicates either a large distance of the transportation of the material, or the fact that the gold has been reworked from nearby local paleoplacers. In the case of the Magua area, considering a large variety of shapes, sizes and the mineral composition of the gold grains, its gold can be of two genetic types: 1) paleoplacer gold, the closest analogue of which is Tarkva deposit in Ghana; 2) indigenous gold, related to ferruginous quartzites, where laterite crusts of weathering are developed. As a result of the roentgenospectrographic (electron microprobe) analysis of gold from different regions, it was found that all of the analysed grains have gold content close to 100%. Due to the results of the analysis, we can affirm that all the samples, except of the sample number 142 are of typical metallic composition of gold, which represent the geochemical features of this element. Sample number 142 is distinguished by its anomalous silver content, which reaches 16.7%.